Integrating Coastal Indigenous Wisdom and Islamic Moral Pedagogy: A Socio-Cultural Study of Fishing Families in Aceh - Safitri Tri Fanny; Suriana; Anisaturrahmi; Marzuki (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study examines the integration of coastal indigenous wisdom and Islamic moral pedagogy in shaping children’s moral character within fishing families in Gampong Ie Meulee, Sabang, Aceh. The study aims to analyze how religious values, maritime customary traditions, and communal social structures interact in sustaining children’s moral education amidst economic vulnerability, globalization, and digital transformation. This research employed a qualitative case study design grounded in an interpretivist-constructivist paradigm. Data were collected through in-depth, semi-structured interviews, participant observation, and documentation techniques involving seven key informants, including fishing parents with children aged 7–12 years, a Panglima Laot customary leader, and village authorities (keucik). The data were analyzed using a thematic analysis approach, which involved coding, categorization, and the development of interpretive themes. The findings reveal that children’s moral formation in the coastal Muslim community is constructed through an interconnected moral ecosystem integrating Islamic spirituality, indigenous maritime traditions, communal social control, and adaptive family resilience. Religious practices, Kenduri Laot, meunasah-based learning, and Panglima Laot customary regulations function as living pedagogical mechanisms that cultivate discipline, honesty, responsibility, gratitude, and social solidarity. The novelty of this study lies in the introduction of the “Sabang Coastal Moral Ecology” concept, which explains how local wisdom and Islamic moral pedagogy interact dynamically within coastal Muslim society. This study contributes theoretically to the global discourse on indigenous Islamic pedagogy and community-based moral education, while practically offering insights for culturally grounded character education policies in vulnerable coastal communities.